Demystifying early carious lesion: A review - Ravi Gupta; Anitha R Kumari; Hunny Sharma; Lipika Jain (Wolters Kluwer Medknow Publications, 2017)
Dental caries is a common disease affecting teeth present in the oral cavity. Dental caries is a disease process resulting in the dissolution of dental hard tissue like enamel and dentin. There has been a change in concept from GV Black's "extension for prevention" to a minimal intervention approach in the recent time. Accurate and reliable detection of early enamel caries is very crucial. The new diagnostic methods and remineralization approach would enable the dentist to detect and diagnose early and direct appropriate preventive measures to promote conservation of the tooth substance. These preventive strategies are much more efficient. The aim of Minimal dentistry is to manage early carious lesion by remineralization. The objective of writing this review on early carious lesion is to understand the early caries disease process and its clinical stages, identification of early caries before there is evidence of surface cavitation through various new technologies and allowing remineralization of such lesion.